Modified current collector and preparation method thereof, electrode plate and negative-electrode-free sodium ion battery
By growing the modified layers of sodium fluoroaluminate and sodium fluorosilicate in situ on the aluminum foil current collector, the problem of fierce sodium dendrites growing at high energy density is solved, and the safety performance and energy density of the battery are improved.
Patent Information
- Application Number
- CN202411799513.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
Sodium ion batteries have fierce growth of sodium dendrites at high energy density, resulting in a risk of battery short circuit, and existing modified current collectors increase battery internal resistance.
Sodium fluoroaluminate and sodium fluorosilicate are grown in situ on the aluminum foil current collector to form a modified layer, reduce the amount of electrolyte injection, reduce dendrites growth, and improve battery safety performance.
Through the use of solid electrolytes, the ion conduction rate is improved, dendrite growth is reduced, the safety performance of the battery is enhanced, the cycle life is extended, and the energy density is improved.
Smart Images

Figure BDA0005177684550000141 
Figure BDA0005177684550000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified current collector and a preparation method thereof, an electrode sheet and a negative electrode-free sodium ion battery. Background Art
[0002] Sodium ion batteries are batteries that use layered oxides (such as nickel iron manganese oxide and copper iron manganese oxide) materials, Prussian blue analogs (such as iron-based Prussian white, etc.), polyanions (such as sodium iron sulfate, sodium iron phosphate, etc.) as positive electrodes, and carbon materials (such as hard carbon, soft carbon) as negative electrodes. They mainly use esters and ethers as solvents. + Metal salts (such as sodium fluoride salts, sodium borate salts and perchlorates) electrolytes and various additives (such as film-forming, flame retardant and overcharge protection) form an electrolyte. Although sodium-ion batteries have the advantages of good low-temperature performance, low cost, high safety and long cycle life, their energy density is still lower than that of lithium-ion batteries. Therefore, under the premise of ensuring battery safety, improving the energy density of sodium-ion batteries has become a more difficult problem.
[0003] However, in the case of a negative electrode-free sodium metal battery with a higher energy density, the growth of sodium dendrites is more violent, and there is a risk of rapid short circuit of the battery, which will seriously hinder the application of sodium ion batteries. Among them, the negative electrode current collector is a key component in the battery. The most common modification is to coat the surface of the aluminum foil with a conductive agent, but it is inevitable to introduce a binder and increase the thickness of the current collector, thereby increasing the internal resistance of the battery.
[0004] Therefore, there is an urgent need to improve the aluminum foil used in sodium-ion batteries to improve the electrochemical performance of the battery while significantly reducing the occurrence of negative electrode failure.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a modified current collector and a preparation method thereof, an electrode sheet and a negative electrode-free sodium ion battery, aiming to extend the battery cycle life and improve the battery energy density and safety.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a modified current collector, comprising a current collector body, a modified layer in-situ grown on the current collector body, and the modified layer contains sodium fluoroaluminate and sodium fluorosilicate.
[0009] In an optional embodiment, in the modified current collector, the thickness of the modified layer is 1 μm-2 μm;
[0010] Preferably, the molar ratio of sodium fluoroaluminate (Na3AlF6) to sodium fluorosilicate (Na2SiF6) is 1:(0.0125-0.05);
[0011] Preferably, the current collector body is selected from at least one of aluminum foil, aluminum mesh and aluminum foam;
[0012] The thickness of the current collector body is 10 μm-20 μm.
[0013] In a second aspect, the present invention provides a method for preparing the modified current collector of the aforementioned embodiment, comprising in-situ growing sodium fluoroaluminate and sodium fluorosilicate on an aluminum foil to form a modified layer.
[0014] In an optional embodiment, it includes:
[0015] The aluminum foil is pre-oxidized to form an aluminum oxide layer on the surface;
[0016] The aluminum oxide layer is used to react to generate aluminum hydroxide on the surface of the aluminum foil;
[0017] The aluminum foil with aluminum hydroxide on the surface is placed in an excess of fluorosilicic acid solution for reaction, and then sodium carbonate is added to continue the reaction to generate sodium fluoroaluminate on the surface; sodium hydroxide is continued to be added to react with the remaining fluorosilicic acid to generate sodium fluorosilicate, and the pH value is adjusted to 6-7 and allowed to stand to grow sodium fluoroaluminate composite sodium fluorosilicate on the surface of the aluminum foil.
[0018] In an optional embodiment, the aluminum foil with sodium fluoroaluminate composite sodium fluorosilicate grown on the surface is calcined;
[0019] Preferably, the calcination temperature is controlled to be 300°C-350°C, the calcination time is 1h-2h, and annealing is performed for 0.5h-2h after the calcination is completed;
[0020] Preferably, the calcining atmosphere is controlled to be an oxygen-containing atmosphere.
[0021] In an optional embodiment, the pre-oxidation process includes: placing the aluminum foil in an oxygen-containing atmosphere for pre-oxidation, controlling the pre-oxidation temperature to be 200° C.-500° C., and the pre-oxidation time to be 1 h-2 h;
[0022] Preferably, before the pre-oxidation treatment, the surface is cleaned with an organic solvent and water respectively, and then acid washing and water washing are performed.
[0023] In an optional embodiment, the process of generating aluminum hydroxide includes: placing an aluminum foil containing an aluminum oxide layer in a sodium hydroxide solution for reaction, taking out the aluminum foil and placing it in a dilute hydrochloric acid solution for reaction;
[0024] Preferably, the concentration of the sodium hydroxide solution is 0.1 mol / L-1.0 mol / L, the reaction temperature in the sodium hydroxide solution is 25° C.-60° C., and the reaction time is 1 h-2 h;
[0025] Preferably, the concentration of the dilute hydrochloric acid solution is 0.1 mol / L-1.0 mol / L, the reaction temperature in the dilute hydrochloric acid solution is 25° C.-60° C., and the reaction time is 1 h-2 h.
[0026] In an optional embodiment, the reaction temperature with the fluosilicic acid solution is 25°C-60°C, and the reaction time is 1h-2h;
[0027] and / or, the molar ratio of the amount of sodium carbonate added to the amount of fluorosilicic acid in the excess fluorosilicic acid solution is 1:(0.1-1), the reaction temperature with sodium carbonate is 25°C-60°C, and the reaction time is 0.5h-3h;
[0028] and / or, the molar ratio of sodium hydroxide added to the fluorosilicic acid in the excess fluorosilicic acid solution is (0.01-0.1):1, the reaction temperature with sodium hydroxide is 25°C-60°C, and the reaction time is 0.5h-3h;
[0029] And / or, adjust the pH value to 6-7 with sodium hydroxide and let it stand for 0.5h-3h.
[0030] In a third aspect, the present invention provides an electrode for a sodium ion battery, comprising a modified current collector according to any one of the aforementioned embodiments or a modified current collector prepared by any one of the preparation methods according to the aforementioned embodiments, wherein a positive electrode active material or a negative electrode active material is coated on the modified current collector;
[0031] Preferably, the positive electrode active material is selected from at least one of sodium iron sulfate and sodium iron pyrophosphate;
[0032] The negative electrode active material is at least one selected from hard carbon, soft carbon and graphite.
[0033] In a fourth aspect, the present invention provides a sodium ion battery comprising the sodium ion battery electrode of the aforementioned embodiment.
[0034] The present invention has the following beneficial effects: the modified current collector provided by the present invention has a current collector body and a modified layer containing sodium fluoroaluminate and sodium fluorosilicate. Since the solid electrolyte sodium fluoroaluminate is in-situ grown on the current collector, it can provide a faster ion conduction rate, thereby reducing the amount of electrolyte injection, reducing the growth of dendrites, and increasing the safety performance of the battery; no binder is used in the in-situ growth process of sodium fluoroaluminate, which is conducive to the uniform deposition of sodium ions. In addition, sodium fluorosilicate is a complexing agent that can complex the free Fe generated by sodium ferric sulfate / sodium ferric pyrophosphate due to charging. 3+ , which can avoid Fe 3+The solid electrolyte and sodium ion battery can be used together to reduce costs, extend cycle life, and improve battery energy density and safety. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0036] Professional term, dendrite: Chinese name dendrite crystal, foreign name dendritic crystal, detailed explanation refers to the dendrite crystal (dendrite) is a crystal that develops in a typical multi-branched tree-like form. Dendritic crystal growth is very common and is illustrated by snow formation and frost patterns on windows. Dendrites form natural fractal patterns.
[0037] Under the high energy density of sodium-ion batteries, the growth of sodium dendrites is more violent, and there is a risk of rapid short circuit of the battery, which will seriously hinder the application of sodium-ion batteries. Among them, the negative electrode current collector is a key component in the battery. The most common modification is to coat the surface of the aluminum foil with a conductive agent, but it is inevitable to introduce a binder and increase the thickness of the current collector, thereby increasing the internal resistance of the battery.
[0038] To this end, the embodiment of the present invention proposes to in-situ grow sodium fluoroaluminate and sodium fluorosilicate on the aluminum foil current collector. The solid electrolyte sodium fluoroaluminate can provide a faster ion conduction rate, thereby reducing the injection amount of the electrolyte, reducing the growth of dendrites, and increasing the safety performance of the battery. No binder is used in the in-situ growth process of sodium fluoroaluminate, which is conducive to the uniform deposition of sodium ions. In addition, sodium fluorosilicate is a complexing agent that can complex the free Fe generated by sodium ferric sulfate / sodium ferric pyrophosphate due to charging. 3+ , which can avoid Fe 3+ Free to the negative electrode, causing the negative electrode to fail.
[0039] The embodiment of the present invention provides a method for preparing a modified current collector, in which sodium fluoroaluminate and sodium fluorosilicate are grown in situ on the current collector body to form a modified layer containing sodium fluoroaluminate and sodium fluorosilicate. The embodiment of the present invention introduces aluminum hydroxide seeds, and then completes the in situ growth of solid electrolyte sodium fluoroaluminate and complexing agent sodium fluorosilicate. The steps are as follows:
[0040] S1. Pre-treatment
[0041] Before the pre-oxidation treatment in step S2, the surface of the current collector body is first cleaned with an organic solvent and water to remove surface impurities; then it is pickled and washed with water to remove the original uneven oxide layer on the surface of the aluminum foil, and then washed with pure water for multiple times to remove the residual acid.
[0042] Specifically, the type of organic solvent is not limited, such as acetone, etc. The type of acid solution used for pickling is not limited, such as dilute hydrochloric acid, dilute sulfuric acid, etc., and the specific concentration can be 0.5 mol / L-1.0 mol / L.
[0043] In some embodiments, the current collector body is selected from at least one of aluminum foil, aluminum mesh and foamed aluminum, and the thickness of the current collector body is 10 μm-20 μm, such as 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, etc.
[0044] S2, pre-oxidation treatment, generating aluminum hydroxide
[0045] The aluminum foil is pre-oxidized to form an aluminum oxide layer on the surface; then, the aluminum oxide layer is used to react to generate aluminum hydroxide on the surface of the aluminum foil. The aluminum hydroxide seeds are evenly distributed on the aluminum foil substrate, and subsequent chemical reactions can in-situ grow sodium fluoroaluminate based on the aluminum source aluminum hydroxide seeds.
[0046] In some embodiments, the pre-oxidation process includes: placing the aluminum foil in an oxygen-containing atmosphere for pre-oxidation, controlling the pre-oxidation temperature to 200°C-500°C, and the pre-oxidation time to 1h-2h. The surface of the aluminum foil is uniformly oxidized in the oxygen-containing atmosphere, and a dense and uniform oxide layer is generated on the surface. Specifically, the oxygen-containing atmosphere can be an air atmosphere, a pure oxygen atmosphere, etc., the reaction process can be carried out in a tubular furnace, and the reaction temperature can be controlled to be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc.; the pre-oxidation time can be 1.0h, 1.5h, 2.0h, etc.
[0047] In some embodiments, the process of generating aluminum hydroxide includes: placing an aluminum foil containing an aluminum oxide layer in a sodium hydroxide solution to react, and sodium aluminate will be generated on the surface of the aluminum foil; after removing the aluminum foil, placing it in a dilute hydrochloric acid solution for reaction, and the sodium aluminate on the surface of the aluminum foil will react with the dilute hydrochloric acid, and aluminum hydroxide will be generated on the surface of the aluminum foil.
[0048] Furthermore, the concentration of the sodium hydroxide solution is 0.1mol / L-1.0mol / L, the reaction temperature in the sodium hydroxide solution is 25°C-60°C, and the reaction time is 1h-2h. By adjusting the concentration, reaction temperature and time of the sodium hydroxide solution, the reaction is fully carried out to generate sodium aluminate on the surface of the aluminum foil. Specifically, the concentration of the sodium hydroxide solution can be 0.1mol / L, 0.3mol / L, 0.5mol / L, 0.8mol / L, 1.0mol / L, etc.; the reaction temperature in the sodium hydroxide solution can be 25°C, 30°C, 40°C, 50°C, 60°C, etc., and the reaction time can be 1.0h, 1.5h, 2.0h, etc.
[0049] Furthermore, the concentration of the dilute hydrochloric acid solution is 0.1mol / L-1.0mol / L, the reaction temperature in the dilute hydrochloric acid solution is 25℃-60℃, and the reaction time is 1h-2h. By adjusting the concentration, reaction temperature and time of the dilute hydrochloric acid, the pH value is more suitable, and the sodium aluminate fully reacts to form aluminum hydroxide. Specifically, the concentration of the dilute hydrochloric acid solution can be 0.1mol / L, 0.3mol / L, 0.5mol / L, 0.8mol / L, 1.0mol / L, etc.; the reaction temperature in the dilute hydrochloric acid solution can be 25℃, 30℃, 40℃, 50℃, 60℃, etc., and the reaction time can be 1.0h, 1.5h, 2.0h, etc.
[0050] It should be added that the sodium hydroxide solution and the dilute hydrochloric acid solution can be reused to reduce the process cost.
[0051] S3, in-situ growth of sodium fluoroaluminate composite sodium fluorosilicate
[0052] Aluminum foil with aluminum hydroxide on its surface is placed in an excess of fluorosilicic acid solution to react. The aluminum hydroxide on the surface of the aluminum foil will react with fluorosilicic acid to form aluminum fluoride. Then, sodium carbonate is added to continue the reaction. Excess fluorosilicic acid will react with sodium carbonate to form sodium fluoride. Sodium fluoride will react with aluminum fluoride formed on the surface of the aluminum foil to form sodium fluoroaluminate, so that sodium fluoroaluminate is evenly deposited on the surface of the aluminum foil. Sodium hydroxide is continued to be added to react with the remaining fluorosilicic acid to form sodium fluorosilicate. Then the pH value is adjusted to 6-7 and allowed to stand for a period of time to allow sodium fluoroaluminate and sodium fluorosilicate to grow evenly on the surface of the aluminum foil.
[0053] Further, the reaction temperature with the fluorosilicic acid solution is controlled to be 25°C-60°C, and the reaction time is 1h-2h, so that aluminum hydroxide and excess fluorosilicic acid fully react to form aluminum fluoride. The molar ratio of the amount of sodium carbonate added to the fluorosilicic acid in the excess fluorosilicic acid solution is 1: (0.1-1), the reaction temperature with sodium carbonate is 25°C-60°C, the reaction time is 0.5h-3h, and the amount of sodium carbonate meets the above range. After the reaction is completed, the remaining part of the fluorosilicic acid and the sodium carbonate fully react to form sodium fluoroaluminate. The molar ratio of the amount of sodium hydroxide added to the fluorosilicic acid in the excess fluorosilicic acid solution is (0.01-0.1): 1, the reaction temperature with sodium hydroxide is 25°C-60°C, the reaction time is 0.5h-3h, and the amount of sodium hydroxide meets the above range, so that the fluorosilicic acid in the system fully reacts and is converted into sodium fluorosilicate.
[0054] Specifically, the molar ratio of the amount of sodium carbonate added to the fluorosilicic acid in the excess fluorosilicic acid solution can be 1:0.1, 1:0.3, 1:0.5, 1:0.8, 1:1.0, etc.; the molar ratio of the amount of sodium hydroxide added to the fluorosilicic acid in the excess fluorosilicic acid solution can be 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.10:1, etc.
[0055] Further, the pH value is adjusted to 6-7 with sodium hydroxide, and the solution is allowed to stand for 0.5h-3h. After standing for a period of time within this pH value range, sodium fluoroaluminate and sodium fluorosilicate can be uniformly grown on the surface of the aluminum foil. Specifically, by adjusting the amount of sodium hydroxide solution, the pH value of the solution in the reaction container is 6.0, 6.3, 6.5, 6.8, 7.0, etc., and the standing time can be 0.5h, 1.0h, 2.0h, 3.0h, etc.
[0056] S4. Calcination
[0057] The aluminum foil with sodium fluoroaluminate composite sodium fluorosilicate grown on the surface is calcined to remove impurities such as excess sodium hydroxide and water, and also improve the crystallinity and toughness of the aluminum foil@sodium fluoroaluminate / sodium fluorosilicate.
[0058] In some embodiments, the calcination temperature is controlled to be 300°C-350°C, the calcination time is 1h-2h, and the annealing is performed for 0.5h-2h after the calcination is completed. The calcination atmosphere can be an oxygen-containing atmosphere, such as air. The crystallinity and toughness of the aluminum foil@sodium fluoroaluminate / sodium fluorosilicate can be further improved by adjusting the calcination temperature, time and other parameters.
[0059] Specifically, the calcination process can be carried out in a muffle furnace, and the calcination temperature can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc.; the calcination time can be 1.0h, 1.5h, 2.0h, etc. After the calcination is completed, annealing is performed, and the temperature is controlled to be lowered in stages, such as being divided into the following cooling stages, such as 300°C, 200°C, 100°C, and room temperature, and the annealing time can be 0.5h, 1.0h, 1.5h, 2.0h, etc.
[0060] The embodiment of the present invention provides a modified current collector, including a current collector body, a modified layer in situ grown on the current collector body, and the modified layer contains sodium fluoroaluminate and sodium fluorosilicate. The solid electrolyte sodium fluoroaluminate grown in situ on the aluminum foil current collector can provide a faster ion conduction rate, thereby reducing the injection amount of the electrolyte, reducing the growth of dendrites, and increasing the safety performance of the battery; sodium fluorosilicate is a complexing agent that can complex the free Fe generated by sodium ferric sulfate / sodium ferric pyrophosphate due to charging. 3+ , which can avoid Fe 3+ Free to the negative electrode, causing the negative electrode to fail.
[0061] In some embodiments, in the modified current collector, the thickness of the modified layer is 1 μm-2 μm, such as 1.0 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2.0 μm, etc.; the molar ratio of sodium fluoroaluminate (Na3AlF6) to sodium fluorosilicate (Na2SiF6) is 1:(0.0125-0.05), such as 1:0.0125, 1:0.0130, 1:0.0150, 1:0.0200, 1:0.0300, 1:0.0400, 1:0.0500, etc. By regulating the mass of the modified layer and regulating the molar ratio of sodium fluoroaluminate to sodium fluorosilicate, the cycle performance and safety performance of the battery are further improved.
[0062] An embodiment of the present invention further provides an electrode for a sodium ion battery, comprising the modified current collector provided in the embodiment of the present invention, wherein the modified current collector is coated with a positive electrode active material or a negative electrode active material. The modified current collector provided in the embodiment of the present invention can be used as a positive electrode current collector and / or a negative electrode current collector of a sodium ion battery, which is beneficial to improving the cycle performance and safety performance of the sodium ion battery.
[0063] Furthermore, the positive electrode active material is selected from at least one of sodium ferric sulfate and sodium ferric pyrophosphate, and the positive electrode active material can be any one or more of the above; the negative electrode active material is selected from at least one of hard carbon, soft carbon and graphite, and the negative electrode active material can be any one or more of the above, or there can be no negative electrode active material.
[0064] An embodiment of the present invention also provides a sodium ion battery, including electrodes for a sodium ion battery, wherein the positive electrode can be prepared by coating a modified current collector with sodium ferric sulfate / sodium ferric pyrophosphate, the negative electrode can be prepared by coating a modified current collector with hard carbon, and the diaphragm can be made of a commercial dry-process PP base film or a wet-process PE base film, injected with a commonly used ester electrolyte, and a soft-pack battery cell is produced by a lamination process.
[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0066] Example 1
[0067] This embodiment provides a modified current collector, and the preparation steps are as follows:
[0068] (1) Purchase commercial aluminum foil (length, width and thickness are 500 mm, 500 mm and 15 mm respectively), wash the aluminum foil with acetone and pure water to remove surface impurities, then soak it in dilute hydrochloric acid (concentration is 0.5 mol / L) to remove the original uneven oxide layer on the surface of the aluminum foil, and then wash it with pure water for several times.
[0069] (2) The aluminum foil treated in step (1) was placed in a tubular furnace, pure O2 was introduced, the temperature was 350°C, and pre-oxidation was carried out for 1.5 hours. The surface of the aluminum foil was uniformly oxidized in a pure O2 environment, and a dense and uniform oxide layer of aluminum oxide was generated on the surface.
[0070] (3) Prepare 0.5 mol / L sodium hydroxide aqueous solution, 0.5 mol / L dilute hydrochloric acid, 0.205 mol / L fluorosilicic acid, and 2.5 mol / L sodium carbonate solution and set aside.
[0071] (4) Prepare a 15L container, put 10L of 0.5mol / L sodium hydroxide solution into it, put the aluminum foil treated in step (2) into the sodium hydroxide solution, and react at 25°C for 2h. Alumina will react with sodium hydroxide and sodium aluminate will be generated on the surface of the aluminum foil.
[0072] (5) Prepare another 15L container, put 10L of 0.5mol / L dilute hydrochloric acid solution into it, place the aluminum foil treated in step (4) in the dilute hydrochloric acid solution, and react at 25°C for 2h. Sodium aluminate will react with the dilute hydrochloric acid, and aluminum hydroxide will be generated on the surface of the aluminum foil.
[0073] (6) Prepare another 15L container, put 10L of 0.205mol / L fluorosilicic acid solution in it, place the aluminum foil treated in step (5) in the fluorosilicic acid solution, and react at 25°C for 2h. The aluminum hydroxide on the surface of the aluminum foil will react with the fluorosilicic acid to form aluminum fluoride. Then add 3mol of sodium carbonate (i.e., add 1.2L of 2.5mol / L sodium carbonate solution) to the container, and react at 25°C for 2h. The excess fluorosilicic acid in the container will react with the sodium carbonate to form sodium fluoride, and the sodium fluoride will react with the aluminum fluoride formed on the surface of the aluminum foil to form sodium fluoroaluminate. The surface of the aluminum foil is uniformly deposited with sodium fluoroaluminate. Then add 0.1mol of sodium hydroxide to the container, and react at 25°C for 2h. It will react with the remaining fluorosilicic acid in the container to form sodium fluorosilicate. Finally, use sodium hydroxide to adjust the pH of the solution to about 6.5 and let it stand for 1h. Finally, sodium fluoroaluminate and sodium fluorosilicate will grow evenly on the surface of the aluminum foil to obtain aluminum foil@sodium fluoroaluminate / sodium fluorosilicate.
[0074] (7) Take out the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate, put it into a muffle furnace, calcine it at 320° C. in air for 1.5 h, and anneal it for 1 h.
[0075] This embodiment also provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, as follows:
[0076] Preparation process of positive electrode: The positive electrode uses a sodium ferrous sulfate oil system formula (with N-methylpyrrolidone as solvent, the solid material composition is sodium ferrous sulfate, PVDF (polyvinylidene chloride), SP (carbon black) and PVP (polyvinyl pyrrolidone), and the mass ratio of sodium ferrous sulfate, PVDF, SP and PVP is 100:7:10:3 to coat the positive electrode. The positive electrode slurry is coated on the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate current collector prepared in this embodiment, and the coating amount is controlled to be 20g / cm 2 , followed by drying;
[0077] Preparation process of negative electrode: select negative electrode-free battery and use carbon-coated aluminum foil for current collection.
[0078] The separator (commercial dry PP base film) was laminated to the positive electrode of the sodium ion battery, and the electrolyte was 1M sodium salt NaPF6 + solvent (diethylene glycol dimethyl ether) to prepare a laminated 5Ah negative electrode-free sodium metal battery.
[0079] Example 2
[0080] This embodiment provides a modified current collector, and the preparation steps are as follows:
[0081] (1) Purchase commercial aluminum foil (length, width and thickness are 500 mm, 500 mm and 15 mm respectively), wash the aluminum foil with acetone and pure water to remove surface impurities, then soak it in dilute hydrochloric acid (concentration is 1 mol / L) to remove the original uneven oxide layer on the surface of the aluminum foil, and then wash it with pure water for several times.
[0082] (2) The aluminum foil treated in step (1) was placed in a tubular furnace, pure O2 was introduced, the temperature was 200°C, and pre-oxidation was carried out for 2.0 hours. The surface of the aluminum foil was uniformly oxidized in a pure O2 environment, and a dense and uniform oxide layer of aluminum oxide was generated on the surface.
[0083] (3) Prepare 0.5 mol / L sodium hydroxide aqueous solution, 0.5 mol / L dilute hydrochloric acid, 0.41 mol / L fluosilicic acid solution, and 2.5 mol / L sodium carbonate solution and set aside.
[0084] (4) Prepare a 15L container, put 10L of 0.5mol / L sodium hydroxide solution into it, put the aluminum foil treated in step (2) into the sodium hydroxide solution, and react at 60°C for 1h. Alumina will react with sodium hydroxide and sodium aluminate will be generated on the surface of the aluminum foil.
[0085] (5) Prepare another 15L container, put 10L of 0.5mol / L dilute hydrochloric acid solution into it, place the aluminum foil treated in step (4) in the dilute hydrochloric acid solution, and react at 60°C for 1h. Sodium aluminate will react with the dilute hydrochloric acid, and aluminum hydroxide will be generated on the surface of the aluminum foil.
[0086] (6) Prepare another 15L container, put 10L of 0.41mol / L fluorosilicic acid solution in it, place the aluminum foil treated in step (5) in the fluorosilicic acid solution, and react at 60°C for 1h. The aluminum hydroxide on the surface of the aluminum foil will react with the fluorosilicic acid to form aluminum fluoride. Then add 6mol of sodium carbonate to the container and react at 60°C for 1h. The excess fluorosilicic acid in the container will react with the sodium carbonate to form sodium fluoride. The sodium fluoride will react with the aluminum fluoride formed on the surface of the aluminum foil to form sodium fluoroaluminate. The surface of the aluminum foil is uniformly deposited with sodium fluoroaluminate. Then add 0.2mol of sodium hydroxide to the container and react at 60°C for 1h. It will react with the remaining fluorosilicic acid in the container to form sodium fluorosilicate. Finally, use sodium hydroxide to adjust the pH of the solution to about 6.0-6.5 and let it stand for 1h. Finally, sodium fluoroaluminate and sodium fluorosilicate will grow uniformly on the surface of the aluminum foil to obtain aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate.
[0087] (7) Take out the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate, put it into a muffle furnace, calcine it at 300° C. in air for 2 h, and anneal it for 0.5 h.
[0088] This embodiment also provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode are made of aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate prepared in this embodiment. The specific steps refer to Example 1.
[0089] Example 3
[0090] This embodiment provides a modified current collector, and the preparation steps are as follows:
[0091] (1) Purchase commercial aluminum foil (length, width and thickness are 500 mm, 500 mm and 15 mm respectively), wash the aluminum foil with acetone and pure water to remove surface impurities, then soak it in dilute hydrochloric acid (concentration is 0.8 mol / L) to remove the original uneven oxide layer on the surface of the aluminum foil, and then wash it with pure water for several times.
[0092] (2) The aluminum foil treated in step (1) was placed in a tubular furnace, pure O2 was introduced, the temperature was 500°C, and pre-oxidation was performed for 1.0 h. The surface of the aluminum foil was uniformly oxidized in a pure O2 environment, and a dense and uniform oxide layer of aluminum oxide was generated on the surface.
[0093] (3) Prepare 0.5 mol / L sodium hydroxide aqueous solution, 0.5 mol / L dilute hydrochloric acid, 0.1025 mol / L fluorosilicic acid solution, and 2.5 mol / L sodium carbonate solution and set aside.
[0094] (4) Prepare a 15L container, put 10L of 0.5mol / L sodium hydroxide solution into it, put the aluminum foil treated in step (2) into the sodium hydroxide solution, and react at 45°C for 1.5h. Alumina will react with sodium hydroxide and sodium aluminate will be generated on the surface of the aluminum foil.
[0095] (5) Prepare another 15L container, put 10L of 0.5mol / L dilute hydrochloric acid solution into it, place the aluminum foil treated in step (4) in the dilute hydrochloric acid solution, and react at 45°C for 1.5h. Sodium aluminate will react with the dilute hydrochloric acid, and aluminum hydroxide will be generated on the surface of the aluminum foil.
[0096] (6) Prepare another 15L container, put 10L of 0.1025mol / L fluorosilicic acid solution in it, place the aluminum foil treated in step (5) in the fluorosilicic acid solution, and react at 45°C for 1.5h. The aluminum hydroxide on the surface of the aluminum foil will react with the fluorosilicic acid to form aluminum fluoride. Then add 1.5mol of sodium carbonate to the container and react at 45°C for 1.5h. The excess fluorosilicic acid in the container will react with the sodium carbonate to form sodium fluoride. The sodium fluoride will react with the aluminum fluoride formed on the surface of the aluminum foil to form sodium fluoroaluminate. The surface of the aluminum foil is uniformly deposited with sodium fluoroaluminate. Then add 0.05mol of sodium hydroxide to the container and react at 45°C for 1.5h. It will react with the remaining fluorosilicic acid in the container to form sodium fluorosilicate. Finally, use sodium hydroxide to adjust the pH of the solution to 6.5-7.0 and let it stand for 1h. Finally, sodium fluoroaluminate and sodium fluorosilicate will grow uniformly on the surface of the aluminum foil to obtain aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate.
[0097] (7) Take out the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate, put it into a muffle furnace, calcine it at 350° C. in air for 1 h, and anneal it for 2 h.
[0098] This embodiment also provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode are made of aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate prepared in this embodiment. The specific steps refer to Example 1.
[0099] Example 4
[0100] The only difference from Example 1 is that the calcination temperature in step (7) is 150°C.
[0101] The results show that the crystallinity of sodium fluoroaluminate / sodium fluorosilicate is low.
[0102] Example 5
[0103] The only difference from Example 1 is that the pre-oxidation in step (2) is carried out in an air atmosphere.
[0104] Comparative Example 1
[0105] This comparative example 1 provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode both use unmodified aluminum foil (see Example 1 for specific parameters). In the preparation process of the positive electrode and the negative electrode, the unmodified aluminum foil is used to replace the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate in Example 1, and the other steps refer to Example 1.
[0106] Comparative Example 2
[0107] The modified current collector provided in this comparative example contains only sodium fluoroaluminate, and the specific steps are as follows:
[0108] (1) Purchase commercial aluminum foil (length, width and thickness are 500 mm, 500 mm and 15 mm respectively), wash the aluminum foil with acetone and pure water to remove surface impurities, then soak it in dilute hydrochloric acid (concentration is 0.5 mol / L) to remove the original uneven oxide layer on the surface of the aluminum foil, and then wash it with pure water for several times.
[0109] (2) The aluminum foil treated in step (1) was placed in a tubular furnace, pure O2 was introduced, the temperature was 350°C, and pre-oxidation was carried out for 1.5 hours. The surface of the aluminum foil was uniformly oxidized in a pure O2 environment, and a dense and uniform oxide layer of aluminum oxide was generated on the surface.
[0110] (3) Prepare 0.5 mol / L sodium hydroxide aqueous solution, 0.5 mol / L dilute hydrochloric acid, 0.2 mol / L fluorosilicic acid, and 2.5 mol / L sodium carbonate and set aside.
[0111] (4) Prepare a 15L container, put 10L of 0.5mol / L sodium hydroxide solution into it, put the aluminum foil treated in step (2) into the sodium hydroxide solution, and react at 25°C for 2h. Alumina will react with sodium hydroxide and sodium aluminate will be generated on the surface of the aluminum foil.
[0112] (5) Prepare another 15L container, put 10L of 0.5mol / L dilute hydrochloric acid solution into it, place the aluminum foil treated in step (4) in the dilute hydrochloric acid solution, and react at 25°C for 2h. Sodium aluminate will react with the dilute hydrochloric acid, and aluminum hydroxide will be generated on the surface of the aluminum foil.
[0113] (6) Prepare another 15L container, put 10L of 0.2mol / L fluorosilicic acid solution into it, place the aluminum foil treated in step (5) in the fluorosilicic acid solution, and react at 25°C for 2h. The aluminum hydroxide on the surface of the aluminum foil will react with the fluorosilicic acid to form aluminum fluoride. Add 3mol of sodium carbonate to the container and react at 25°C for 2h. The excess fluorosilicic acid in the container will react with the sodium carbonate to form sodium fluoride, and the sodium fluoride will react with the aluminum fluoride generated on the surface of the aluminum foil to form sodium fluoroaluminate. A uniform sodium fluoroaluminate is deposited on the surface of the aluminum foil. Finally, use sodium hydroxide to adjust the pH of the solution to about 6.5 and let it stand for 1h. Finally, sodium fluoroaluminate and sodium fluorosilicate will grow uniformly on the surface of the aluminum foil to obtain aluminum foil@sodium fluoroaluminate.
[0114] (7) Take out the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate, put it into a muffle furnace, calcine it at 320° C. in air for 1.5 h, and anneal it for 1 h.
[0115] This comparative example also provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode utilize the modified current collector prepared in this comparative example. The specific steps refer to Example 1.
[0116] Comparative Example 3
[0117] The modified current collector provided in this comparative example contains only sodium fluorosilicate, and its preparation steps are as follows:
[0118] (1) Purchase commercial aluminum foil (length, width and thickness are 500 mm, 500 mm and 15 mm respectively), wash the aluminum foil with acetone and pure water to remove surface impurities, then soak it in dilute hydrochloric acid (concentration is 0.5 mol / L) to remove the original uneven oxide layer on the surface of the aluminum foil, and then wash it with pure water for several times.
[0119] (2) Prepare 0.5 mol / L sodium hydroxide aqueous solution, 0.5 mol / L dilute hydrochloric acid, 0.205 mol / L fluorosilicic acid, and 2.5 mol / L sodium carbonate and set aside.
[0120] (3) Prepare another 15L container, put 10L of 0.005mol / L fluorosilicic acid solution in it, place the aluminum foil in the fluorosilicic acid solution, add 0.1mol sodium hydroxide into the container, react at 25°C for 2h, react with the remaining fluorosilicic acid in the container to generate sodium fluorosilicate, and finally adjust the pH of the solution to about 6.5 with sodium hydroxide and let it stand for 1h. Finally, the surface of the aluminum foil will be compounded with sodium fluorosilicate, and aluminum foil / sodium fluorosilicate will be obtained.
[0121] (4) Take out the aluminum foil @ sodium fluorosilicate, put it into a muffle furnace, calcine it at 320° C. in air for 1.5 h, and anneal it for 1 h.
[0122] This comparative example also provides a sodium ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode utilize the modified current collector prepared in this comparative example. The specific steps refer to Example 1.
[0123] Test Example 1
[0124] The electrochemical performance of the sodium ion batteries provided in the examples and comparative examples was tested, and the results are shown in Table 1.
[0125] Table 1 Electrochemical performance of sodium ion batteries provided in Examples and Comparative Examples
[0126]
[0127]
[0128] It can be seen from Table 1 that the sodium ion battery prepared in the embodiment of the present invention has more excellent electrochemical performance.
[0129] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified current collector, characterized in that: The invention comprises a current collector body, on which a modified layer is in-situ grown, and the modified layer contains sodium fluoroaluminate and sodium fluorosilicate.
2. The modified current collector according to claim 1, characterized in that: In the modified current collector, the thickness of the modified layer is 1 μm-2 μm; Preferably, the molar ratio of sodium fluoroaluminate to sodium fluorosilicate is 1:(0.0125-0.05); Preferably, the current collector body is selected from at least one of aluminum foil, aluminum mesh and aluminum foam; The thickness of the current collector body is 10 μm-20 μm.
3. A method for preparing the modified current collector according to claim 1 or 2, characterized in that: The method comprises in-situ growing sodium fluoroaluminate and sodium fluorosilicate on the current collector body to form the modified layer.
4. The preparation method according to claim 3, characterized in that: The current collector body is aluminum foil, and the preparation method comprises: The aluminum foil is pre-oxidized to form an aluminum oxide layer on the surface; The aluminum oxide layer is used to react to generate aluminum hydroxide on the surface of the aluminum foil; The aluminum foil with aluminum hydroxide on the surface is placed in an excess of fluorosilicic acid solution for reaction, and then sodium carbonate is added to continue the reaction to generate sodium fluoroaluminate on the surface; sodium hydroxide is continued to be added to react with the remaining fluorosilicic acid to generate sodium fluorosilicate, and the pH value is adjusted to 6-7 and allowed to stand to grow sodium fluoroaluminate composite sodium fluorosilicate on the surface of the aluminum foil.
5. The preparation method according to claim 4, characterized in that: calcining the aluminum foil with sodium fluoroaluminate composite sodium fluorosilicate grown on the surface; Preferably, the calcination temperature is controlled to be 300°C-350°C, the calcination time is 1h-2h, and annealing is performed for 0.5h-2h after the calcination is completed; Preferably, the calcining atmosphere is controlled to be an oxygen-containing atmosphere.
6. The preparation method according to claim 4, characterized in that: The pre-oxidation treatment process includes: placing the aluminum foil in an oxygen-containing atmosphere for pre-oxidation, controlling the pre-oxidation temperature to be 200° C.-500° C., and the pre-oxidation time to be 1 h-2 h; Preferably, before the pre-oxidation treatment, the surface is cleaned with an organic solvent and water respectively, and then acid washing and water washing are performed.
7. The preparation method according to claim 4 or 6, characterized in that: The process of generating aluminum hydroxide comprises: placing the aluminum foil containing the aluminum oxide layer in a sodium hydroxide solution for reaction, taking out the aluminum foil and placing it in a dilute hydrochloric acid solution for reaction; Preferably, the concentration of the sodium hydroxide solution is 0.1 mol / L-1.0 mol / L, the reaction temperature in the sodium hydroxide solution is 25° C.-60° C., and the reaction time is 1 h-2 h; Preferably, the concentration of the dilute hydrochloric acid solution is 0.1 mol / L-1.0 mol / L, the reaction temperature in the dilute hydrochloric acid solution is 25° C.-60° C., and the reaction time is 1 h-2 h.
8. The preparation method according to claim 4, characterized in that: The reaction temperature with the fluosilicic acid solution is 25°C-60°C, and the reaction time is 1h-2h; and / or, the molar ratio of the amount of sodium carbonate added to the amount of fluorosilicic acid in the excess fluorosilicic acid solution is 1:(0.1-1), the reaction temperature with sodium carbonate is 25°C-60°C, and the reaction time is 0.5h-3h; and / or, the molar ratio of sodium hydroxide added to the fluorosilicic acid in the excess fluorosilicic acid solution is (0.01-0.1):1, the reaction temperature with sodium hydroxide is 25°C-60°C, and the reaction time is 0.5h-3h; And / or, adjust the pH value to 6-7 with sodium hydroxide and let it stand for 0.5h-3h.
9. An electrode sheet, characterized in that: A modified current collector comprising any one of claims 1 to 2 or a modified current collector prepared by the preparation method of any one of claims 3 to 8, wherein the modified current collector is coated with a positive electrode active material or a negative electrode active material; Preferably, the positive electrode active material is selected from at least one of sodium iron sulfate and sodium iron pyrophosphate; The negative electrode active material is selected from at least one of hard carbon, soft carbon and graphite.
10. A negative electrode-free sodium ion battery, characterized in that: The sodium ion battery electrode according to claim 9.